2015
DOI: 10.1016/j.cyto.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osteopontin in acute liver failure

Abstract: Background Osteopontin (OPN) is a novel phosphoglycoprotein expressed in Kupffer cells that plays a pivotal role in activating natural killer cells, neutrophils and macrophages. Measuring plasma OPN levels in patients with acute liver failure (ALF) might provide insights into OPN function in the setting of massive hepatocyte injury. Methods OPN levels were measured using a Quantikine® ELISA assay on plasma from 105 consecutive ALF patients enrolled by the US Acute Liver Failure Study Group, as well as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 29 publications
1
39
2
Order By: Relevance
“…The increase in OPN observed in this study is in contrast to recent data demonstrating that patients with acute liver failure (from various etiologies) who died/received a transplant had reduced levels of plasma OPN compared with those who recovered . The difference between these studies may be related to the timing of sample collection.…”
Section: Discussioncontrasting
confidence: 99%
“…The increase in OPN observed in this study is in contrast to recent data demonstrating that patients with acute liver failure (from various etiologies) who died/received a transplant had reduced levels of plasma OPN compared with those who recovered . The difference between these studies may be related to the timing of sample collection.…”
Section: Discussioncontrasting
confidence: 99%
“…Elevated levels of OPN may simply correlate with the extent of hepatocyte loss not otherwise reflected in biomarkers such as TBIL. It is of note that the association of liver failure with the increase in OPN levels observed in this study contrasts with data demonstrating that patients with acute liver failure (from various etiologies) who died or received a transplant had reduced levels of plasma OPN compared with those who recovered . The difference between this study and the DILIN study may be related to the timing of the sample collection.…”
Section: Promising New Dili Biomarkerscontrasting
confidence: 93%
“…It is of note that the association of liver failure with the increase in OPN levels observed in this study contrasts with data demonstrating that patients with acute liver failure (from various etiologies) who died or received a transplant had reduced levels of plasma OPN compared with those who recovered. 80 The difference between this study and the DILIN study may be related to the timing of the sample collection. Entry into the previously conducted studies required acute liver failure to be occurring at enrollment (INR ≥1.5…”
Section: Prognostic Biomarkersmentioning
confidence: 91%
“…Previous studies have demonstrated that two forms of OPN coexist: An intracellular form (iOPN) and a secreted form (sOPN) (15,29,30). Although sOPN was measured in the present study, further studies are imperative to investigate the role of iOPN in lymphocytes and dendritic cells.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, in mice models of liver injury induced by diethylnitrosamine or ischemia/reperfusion, OPN exerted a protective effect by ameliorating the production of IL-6 and TNF-α in macrophages and inhibiting inflammation (11,12). Furthermore, OPN may serve a key role in the expansion of hepatic progenitor cells (HPC) and in promoting liver regeneration during liver cancer (13,14) and acute liver failure (15,16).…”
Section: Introductionmentioning
confidence: 99%